Toefl success - Rogers, Bruce; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2004)
Listening Comprehension; Structure and Written Expression; Reading Comprehension.
Keywords: Toeft CTB; English language -- Tests; English language -- Study and teaching -- Textbooks for foreign speakers